Economic costs of rabies post exposure prophylaxis - Hardanahalli, Ravish Shankaraiah; Annadani, Rachana Rajashekhara; Undi, Malatesh; Vijayashanakar, Veena; Banerjee, Rupsa; Mandya, Ramya P (Indian Journal of Community Health, 2017)
Background: The highest financial expenditure for Rabies in any country is the cost of rabies post-exposure prophylaxis. The type of vaccine and route of administration, as well as type of immunoglobulin used, all significantly influences the cost of treatment. Aims & Objective: To analyse the direct and indirect cost of the rabies post exposure prophylaxis. Material & Methods: The study was conducted at anti-rabies clinics of Government Hospital, where PEP is provided free of cost and a private medical college hospital, where PEP is provided for a cost. 290 animal bite victims who completed the PEP were included in the study. After obtaining written informed consent from the study subjects, data regarding socio-demographic profile, details of animal bite exposure, cost incurred for PEP i.e, direct and indirect cost were collected. Results were expressed as proportions, median and inter-quartile range (Q1-Q3). Results: The total median cost incurred by the bite victims for PEP in Government hospitals was Rs.585 with Q1-Q3 of Rs.444-725 and the cost spent by the government was Rs. 1031; whereas the total cost incurred in private hospital was Rs.5200 with Q1-Q3 of Rs.4900-5701.Conclusion: PEP has a significant economic burden to the bite victims, especially for poor people living of the developing World.